Design, Fabrication and Testing of New Invented Spring Sickle Pole "ZappIt®" for Palm Harvesting - Zamzuri, Hamedon; M. Nafis, O. Z.; Z., Ghazalli; M. M., Noor (2008)

(untitled)
A new harvesting pole, specifically designed for palms trees, was designed, developed and tested. It comprises three sections, the locking, extension and spring sickle, which were joined through an aluminum pole. The pole can be adjusted to certain length to reach different height of tree. It is built using standard circular rod with cross section diameters of 50 mm. This newly invented spring sickle pole called ZappItÂ® has been designed based on the ordinary sickle widely used in Malaysia palm estates. ZappItÂ® introduced new mechanism concept of spring compression as a source of mechanical force to cut the frond and fruit bunch. The locking system was designed and located at the bottom of the pole for manual hand operated. While the threaded steel used to link the locking systems and spring sickle system.